2010
DOI: 10.1152/ajplung.00298.2009
|View full text |Cite
|
Sign up to set email alerts
|

20-HETE-induced nitric oxide production in pulmonary artery endothelial cells is mediated by NADPH oxidase, H2O2, and PI3-kinase/Akt

Abstract: . 20-HETE-induced nitric oxide production in pulmonary artery endothelial cells is mediated by NADPH oxidase, H2O2, and PI3-kinase/Akt. Am J Physiol Lung Cell Mol Physiol 298: L564 -L574, 2010. First published January 8, 2010 doi:10.1152/ajplung.00298.2009We have shown that 20-hydroxyeicosatetraenoic acid (20-HETE) increases both superoxide and nitric oxide (NO) production in bovine pulmonary artery endothelial cells (BPAECs). The current study was designed to determine mechanisms underlying 20-HETE-stimulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 37 publications
3
24
0
1
Order By: Relevance
“…Phosphorylation of serine 1177 has been associated with increased synthesis of nitric oxide (Butt et al, 2000), and we found that it was markedly increased in EPCs treated with 20-HETE just as others reported in ECs (Cheng et al, 2008;Bodiga et al, 2010), pointing out the close similarities between these progenitor cells and mature ECs. Both the proliferative and the migratory effects of 20-HETE could be directly due to stimulation of some unknown receptor (Miyata and Roman, 2005), or they might be secondary to increases in nitric oxide and VEGF (Sautina et al, 2010).…”
Section: Cyp4a/f-20-hete and Endothelial Precursor Cell Functions 425supporting
confidence: 81%
“…Phosphorylation of serine 1177 has been associated with increased synthesis of nitric oxide (Butt et al, 2000), and we found that it was markedly increased in EPCs treated with 20-HETE just as others reported in ECs (Cheng et al, 2008;Bodiga et al, 2010), pointing out the close similarities between these progenitor cells and mature ECs. Both the proliferative and the migratory effects of 20-HETE could be directly due to stimulation of some unknown receptor (Miyata and Roman, 2005), or they might be secondary to increases in nitric oxide and VEGF (Sautina et al, 2010).…”
Section: Cyp4a/f-20-hete and Endothelial Precursor Cell Functions 425supporting
confidence: 81%
“…NADPH oxidase activity in kidney cortex (homogenized in PBS containing a phosphatase inhibitor cocktail from Roche Applied Sciences) of mice was quantified using a lucigenin-enhanced chemiluminescence assay using a single-tube luminometer (Berthold FB12, Berthold Technologies) with NADPH (1 mM) and lucigenin (50 M) at 37°C as previously described (39). The specific peptide inhibitor of NOX2, gp91phox ds tat (50 M), was used to confirm superoxide generation from NADPH oxidase (5,40). Dihydroethidium (DHE), an oxidative fluorescent dye, was used to measure superoxide levels in kidney samples as previously described (39).…”
Section: Methodsmentioning
confidence: 99%
“…In NADPH oxidaseknockout (p47(phox−/−)) mice reduced NOS3 phosphorylation was observed and VEGF-mediated coronary vasodilatation was impaired [15]. Moreover, the addition of 20-hydroxyeicosatetraenoic acid (20-HETE) to endothelial cells activated NOS3 through generation of ROS and PI3Kinase/Akt phosphorylation [6]. The sequential generation of ROS and NO observed in the present study may represent the physiological condition of NOS3 activation and may circumvent the uncoupling of NOS3 with the result of oxidative stress which occurs under pathophysiological conditions, e.g.…”
Section: Discussionmentioning
confidence: 99%